Arminizacion NIIFF front NICSP (2014)
With the world trend of economic political social internationalization, there arises the need to create and adopt standards to regulate the different kind of exchange; the countable financial sector is not strange to this reality, for which international institutions of technical recognition where there are projecting models and who looks for the standardization by means of the adoption of international procedure of accounting where it specifies a certain conceptual frame for the accounting process.